Exploring Latina Clinical Mental Health Counseling Students’ Perceptions of Teaching Practices - Javier Cavazos Vela; Jeremiah Fisk; James Ikonomopoulos (Teaching and Supervision in Counseling, 2019)
Researchers conducted in-depth interviews with clinical mental health counseling students to understand perceptions of their instructors’ teaching practices. Using an-evidenced based teaching model as a theoretical lens (Malott et al., 2014), researchers highlighted students’ experiences, perceptions, and beliefs regarding teaching. Following a discussion, recommendations for researchers and counselor educators to improve teaching practices are provided.
Keywords: Teaching; clinical mental health counseling students; counselor education